Population structure of the Brazilian Crioula Lageana cattle (Bos taurus) breed - Pezzini, Tomaz; Mariante, Arthur S.; Martins, Edison; Paiva, Samuel; Seixas, Luiza; G. Costa Jr, João B.; Rolo, Jivago; McManus, Concepta (Revista Colombiana de Ciencias Pecuarias, 2018)
Background: The lack of information on population structure is one of the main obstacles to develop breeding and conservation programs for animal genetic resources. Objective: To characterize the population structure of Crioula Lageana cattle breed (Bos taurus) in order to assess its genetic diversity. Methods: Database with information of 1,638 Crioula Lageana animals, collected during 38 years, was analysed using the ENDOG v.4.4 program. Results: Effective population size ranged from 72.53 in complete generations to 143.90 in maximum generations. Inbreeding and Average Relatedness coefficients were 0.34 and 0.91%, respectively. The effective number of founders and ancestors were 29 and 28 animals, respectively, and only ten ancestors were responsible for 50% of the genetic variability of the whole population. The average generation interval was 5.84 years in the paternal line and 7.70 in the maternal one. Wright´s F statistics indicated low genetic distances between subsets in relation to the total population (Fst = 0.0015), between individuals with respect to their subpopulation (Fis = -0.0027), and between individuals in relation to the total population (Fit = -0.0012). Conclusion: Analysis of the population indicated that, despite the small number of animals with known parentage and considerable loss of genetic variability by the constant use of a few sires, and same value of number of founders and ancestors, the population showed good genetic management, low inbreeding, low genetic differentiation among subpopulations, and probably adequate effective population size for breed preservation.